PEOPLE'S EDUCATION: IMPROVING UNDERSTANDING OF THE HEALTHY AND SAFE INTERNET FOR STUDENTS OF KEUPULA DUA STATE PRIMARY SCHOOL - Rahman, Aulia; Prasetyo, Okhaifi; Anis, Madhan (Universitas Airlangga, 2024)
Education in the digital era is currently experiencing rapid development, where the internet has become one of the primary sources of information. However, unwise use of the internet can have a negative impact, especially on students at the elementary school (SD) level. Therefore, Samudra University lecturers and students are committed to carrying out Community Service (PKM) at the Matang Keupula Dua Elementary School. This activity aims to increase students' understanding and awareness of the importance of a healthy and safe internet. There are three stages in implementing healthy and safe internet education activities: the preparation stage, implementation stage, and evaluation stage (data collection and data analysis). The results of the implementation of community service activities, which lasted for one day, received a positive response from the training participants, both students and teachers. This Community Service Program (PKM) can be considered successful and implemented in accordance with the proposed targets. Thus, 29 students' knowledge regarding healthy and safe internet use increased by 27%.